PENGEMBANGAN EKONOMI DESA MELALUI INOVASI G’CHIPS BERBASIS POTENSI LOKAL DAN PEMASARAN DIGITAL MENUJU MASYARAKAT PRODUKTIF - Hamzah Tkella, Wahid Holik; Jamaludin, Muhammad; Nurelisah; Sundari, Deoh; Rizki Ananda, Della; Permata Sari, Siska; Diana Nurhayati, Dina; Wahdiyana, Fika (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2023)
This research aims to increase productivity and business diversity and provide facilities and facilities to support the improvement of the village economy. The method used in this research is a qualitative descriptive method. This research was carried out by Des Cijujung RW 02 RT 01 using observation and interview techniques as well as documentation with the Cijujung village government and the local farming community. As a result of this research, students determined and made double-leaf plants or chives as an innovative idea to be tested and used as double-leaf chips/chives or what are called G'Chips. The achievements obtained apart from improving the economy of the Cijujung village community, also increase the ideas and productivity of the local community which can be carried out independently and sustainably for the Cijujung village community